Peritoneal Dialysis Treatment Modality Option in Acute Kidney Injury - Ponce, Daniela [UNESP] (2017)
Background: Peritoneal dialysis (PD) may be a feasible and safe alternative to haemodialysis not only in the chronic but also in the acute setting. It was previously widely accepted as a modality for acute kidney injury (AKI) treatment, but its practice declined in favor of other types of extracorporeal therapies. Summary: The interest in PD to manage AKI patients has been increased and PD is now frequently used in developing countries because of its lower cost and minimal infrastructural requirements. Studies from these countries have shown that, with careful thought and planning, critically ill patients can be successfully treated using PD. Some of the classic limitations of PD use in AKI, such as infectious and mechanical complications and poor metabolic control, have been decreased with the use of cyclers, flexible catheters, and a high volume of dialysate. The recent publication of the International Society of Peritoneal Dialysis guidelines for PD in AKI has tried to address these issues and provide an evidence-based standard by which to initiate therapy. Key Message: In this review, advances in technical aspects and the advantages and limitations of PD were discussed; it clearly showed that PD is a simple, safe, and efficient way to correct metabolic, electrolyte, acid-base, and volume disturbances generated by AKI and it can be used as a renal replacement therapy modality to treat AKI, both in and out of the intensive care unit setting.